MANAJEMEN PRODUKSI SIARAN BERITA DI PADANG TV - Faudzi, Ahmad; Fajri, Muhamad (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
This research analyzes News Production Management at Padang TV using the POAC (Planning, Organizing, Actuating, Controlling) approach and evaluates the dominance of news broadcast time compared to other programs. The research method used is descriptive qualitative through interviews, observation and document analysis. In planning, Padang TV sets the editorial strategy, topic selection and coverage schedule. Organizing involves the formation of an editorial team with an efficient division of tasks. Implementation is done through team coordination and utilization of technology to present accurate and timely news. Controlling includes regular evaluation of the content and production process. The results show that the dominance of news broadcast time is due to the high public need for up-to-date information. In conclusion, the implementation of effective news production management with POAC plays an important role in Padang TV's success in providing quality information.